Low serum dehydroepiandrosterone is associated with diabetic dyslipidemia risk in males with type 2 diabetes - Chen, Shanshan; Li, Shuo; Zhang, Xinxin; Fan, Yuxin; Liu, Ming (Frontiers in Endocrinology, 2023)
Objective: Sex steroid hormones are associated with the advancement of metabolic diseases such as dyslipidemia. This cross-sectional study aimed to investigate the relationship between dehydroepiandrosterone, dehydroepiandrosterone sulfate, androstenedione, and testosterone levels and the risk of dyslipidemia in people with type 2 diabetes mellitus. Materials and Methods: The analysis included 1,927 patients with type 2 diabetes mellitus. Serum dehydroepiandrosterone, dehydroepiandrosterone sulfate, androstenedione, and testosterone levels were determined using lipid chromatography-tandem mass spectrometry. Multivariable analyses were performed to investigate the association between the variables and dyslipidemia. Results: The multivariable-adjusted odds ratio (OR) and 95% confidence interval (CI) of dyslipidemia across DHEA tertiles were 0.39 and 0.24-0.64, respectively (p trend = 0.001). This relationship was still maintained when analyzed as a continuous variable (odds ratio, 0.96; 95% confidence interval, 0.92–0.99; P < 0.01). However, in males with type 2 diabetes mellitus, no significant correlations were found between rising levels of dehydroepiandrosterone sulfate, androstenedione, and total testosterone and the risk of dyslipidemia (all P > 0.05). Furthermore, there was no significant association between androgen precursors and total testosterone with regard to the risk of developing dyslipidemia (all P > 0.05). Conclusions: Serum dehydroepiandrosterone levels were substantially and adversely correlated with dyslipidemia in adult men with T2DM. These results indicated that dehydroepiandrosterone may have an essential role in the development of dyslipidemia. More prospective research is required to validate this link. Keywords: dehydroepiandrosterone; dehydroepiandrosterone sulfate, dyslipidemia; diabetes mellitus, type 2, androgen